Development of combinatorial antibody therapies for diffuse large B cell lymphoma - Geanes, Eric S.; Krepel, Stacey A.; McLennan, Rebecca; Pierce, Stephen; Khanal, Santosh; Bradley, Todd (Frontiers in Medicine, 2022)
Diffuse large B-cell lymphoma (DLBCL), the most common form of lymphoma, is typically treated with chemotherapy combined with the immunotherapy rituximab, an antibody targeting the B cell receptor, CD20. Despite the success of this treatment regimen, approximately a third of DLBCL patients experience either relapse or have refractory disease that is resistant to rituximab, indicating the need for alternative therapeutic strategies. Here, we identified that CD74 and IL4R are expressed on the cell surface of both CD20 positive and CD20 negative B cell populations. Moreover, genes encoding CD74 and IL4R are expressed in lymphoma biopsies isolated from all stages of disease. We engineered bispecific antibodies targeting CD74 or IL4R in combination with rituximab anti-CD20 (anti-CD74/anti-CD20 and anti-IL4R/anti-CD20). Bispecific antibody function was evaluated by measuring direct induction of apoptosis, antibody-dependent cellular phagocytosis, and antibody-dependent cellular cytotoxicity in both rituximab-sensitive and rituximab-resistant DLBCL cell lines. Both anti-CD74/anti-CD20 and anti-IL4R/anti-CD20 were able to mediate ADCC and ADCP, but CD74-targeting therapeutic antibodies could also mediate direct cytotoxicity. Overall, this study strongly indicates that development of bispecific antibodies that target multiple B cell receptors expressed by lymphoma could provide improved defense against relapse and rituximab resistance.